Passion Fruit Seed Oil: A Sustainable Feedstock for Additive Manufacturing of Renewable Polymers - dos Santos, Gabriel Iago [UNESP]; Gaglieri, Caroline [UNESP]; Alarcon, Rafael Turra; Magri, Raquel [UNESP]; Hartlieb, Matthias; Bannach, Gilbert [UNESP] (Springer Nature, 2024)
Vegetable oils show a strong potential as renewable resources for developing new monomers and polymers. Unsaturated fatty acids offer opportunities for chemical modifications such as epoxidation and acrylation. In parallel, the rise of additive manufacturing, particularly 3D printing by stereolithography process, provides a green approach for the fabrication of polymeric materials with diverse architectures and shapes for various fields, including biomedical, electronics, and aerospace. This work reports the synthesis and application of a novel 3D printable, renewable biomass-derived monomer obtained from passion fruit vegetable oil. We comprehensively assessed its conversion under different monomeric mixtures containing type 1 or type 2 photoinitiators under ultraviolet and blue irradiations. The mixture containing type 1 photoinitiator demonstrated superior performance under UV light and was further characterized for its suitability as a 3D printing resin. Subsequent investigations revealed that a photoinitiator concentration as low as 0.5 wt.% suffices for effective 3D printing. Our findings demonstrate the feasibility of utilizing this passion fruit vegetable oil-derived, renewable monomer for additive manufacturing of bio-based polymers while minimizing the dependence on photoinitiators. Graphical Abstract: (Figure presented.)
Keywords: 3D printing; Addictive manufacturing; Bio-based polymers; Passion fruit vegetable oil